The effect of body weight, body condition score and parity on the intensity of oestrus expression in saanen does - Shekinah Shamini Victor (2015)
A sample size of 14 Saanen does were used to conduct this research on the effect of parity, BCS and body weight on the intensity of oestrus expression. The does were grouped into two groups of seven each and Controlled Internal Drug Release (CIDR) was administered to synchronise the oestrus expression in all does by group. After 14 days, the CIDR was removed. The intensity of oestrus expression was observed for the does one group at a time from 9am to 6pm for three consecutive days. There is no significant (p<0.05) effect on intensity of oestrus expression for parity, BCS and body weight for the physical oestrus characteristics. Physical oestrus expressions which are reddening of vulva, swelling of vulva and vaginal discharge are common signs of oestrus. The parity, BCS or body weight of goats have very little or no effect on the intensity of these physical signs. Parity showed significance (P<0.05) for the behavioural characteristic wagging of tail. Parity of 3 or more shows the highest intensity for the wagging of tail behavioural characteristic, followed by parity 0 and lastly parity 1 to 2. BCS showed significance (P<0.05) for the behavioural characteristics vocalization, wagging of tail, mounted but not standing and standing heat. BCS for 4≥Y≥5 shows the greatest intensity, followed by BCS 1.0≥Y≥2.0 and BCS 2.5≥Y≥3.5. Body weight showed significance (P<0.05) for the behavioural characteristics sniffing or rubbing against herd mates and mounting other goats. Body weight has effect on the intensity of oestrus expression. However, there is no specific body weight that shows the greatest or least intensity. Parity, BCS and body weight has effect on the intensity of oestrus expression.